Bernstein-Type Operators - Ali, Kawa Sardar Mohammad (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
In this work we are interested in the approximation of some type of operators called Bernstein-type. For this purpose, the operator  ,  0,  n L f x f C  called the Bernstein-type approximation operator is considered. The aim is to use some probabilistic properties to improve and sharp to operator defined above. Also, the rates of convergence as well as the continuity of the operator are studied. Various methods of approaching the problem are evaluated in this study. Keywords: Bernstein type operator, probabilistic approach, binomial distribution, rates of convergence.

ÖZ : Bu çalışmada Bernstein - tipi operatörlerin yaklaşımlarıyla ilgilenilimiştir.Bunun için  ,  0,  n L f x f C  olarak belirtilen Bernstein tipi yaklaşım operatörü ele alınmıştır. Yukarıda verilen operatör için bazı olasılıksal metodlar kullanılarak yaklaşım özellikleri çalışılmıştır. Ayrıca, yakınsama hızı yanı sıra operatörün sürekliliği incelenmiş olup farklı yöntemlerle yaklaşım problemi de bu çalışmada değerlendirilmiştir. Anahtar kelimeler: Bernstein tipi operatörler, olasılıksal yaklaşım, binom dağılımı, yaklaşım hızı.
Master of Science in Mathematics. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Arts and Sciences, Dept. of Mathematics, 2016. Supervisor: Prof. Dr. Sonuç Zorlu Oğurlu.
Keywords: Mathematics; Mathematical Operators; Bernstein type operator; probabilistic approach; binomial distribution; rates of convergence